2017
DOI: 10.1371/journal.pone.0186292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fire frequency on litter decomposition as mediated by changes to litter chemistry and soil environmental conditions

Abstract: Litter quality and soil environmental conditions are well-studied drivers influencing decomposition rates, but the role played by disturbance legacy, such as fire history, in mediating these drivers is not well understood. Fire history may impact decomposition directly, through changes in soil conditions that impact microbial function, or indirectly, through shifts in plant community composition and litter chemistry. Here, we compared early-stage decomposition rates across longleaf pine forest blocks managed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…By contrast, wildfire studies indicate that transitions of fungal communities from ‘burned’ to ‘unburned’ states can take more than a decade (Dooley & Treseder, ; Holden et al ., ; Oliver et al ., ). Decomposition data here indicate that fire effects on microbial decomposition may be important, albeit transient, compared with fire regime impacts through litter stoichiometry (Ficken & Wright, ; Butler et al ., ). These differences suggest that variation in fire return intervals and/or fire intensities may have large effects on microbial community dynamics and function.…”
Section: Discussionmentioning
confidence: 97%
“…By contrast, wildfire studies indicate that transitions of fungal communities from ‘burned’ to ‘unburned’ states can take more than a decade (Dooley & Treseder, ; Holden et al ., ; Oliver et al ., ). Decomposition data here indicate that fire effects on microbial decomposition may be important, albeit transient, compared with fire regime impacts through litter stoichiometry (Ficken & Wright, ; Butler et al ., ). These differences suggest that variation in fire return intervals and/or fire intensities may have large effects on microbial community dynamics and function.…”
Section: Discussionmentioning
confidence: 97%
“…However, our LME modeling approach allowed us to examine the effects of fire regime × resource limitation interactions on decomposition while accounting for the more general effects of fire regime. Moreover, reciprocal litter transplant studies have shown litter chemistry to be a significant driver of decomposition in fire‐affected ecosystems (Ficken and Wright ). Thus, without discounting the critical roles of moisture and other environmental factors, our study provides robust evidence that the stoichiometric imbalances associated with increasingly frequent fire can exert strong, constraining influences on decomposition.…”
Section: Discussionmentioning
confidence: 99%
“…Any alteration of the foliage by the prescribed fire appeared to have an ephemeral influence on decomposition and, by the end of the study, total mass loss was similar between foliar litter sources. Changes in decomposition rates with long-term use of prescribed fire have frequently been attributed to changes in N and thus litter quality (Hernández and Hobbie 2008;Brennan et al 2009;Ficken and Wright 2017). Litter quality characteristics such as C:N and lignin: N did Table 3 Mean organic matter loss on ignition (LOI; g kg −1 ) and ash-free concentrations of six nutrients (carbon, C; nitrogen, N; phosphorus, P; potassium, K; calcium, Ca; and magnesium, Mg) for pine foliar litter collected from three loblolly-shortleaf pine stands prior to a 472-day study (24 Feb 2000to 10 Jun 2001 not significantly differ between litter sources in our study.…”
Section: Decompositionmentioning
confidence: 99%
“…Litter decomposition rates have also been found to be well correlated with litter N content and C:N ratios (Taylor et al 1989;Enríquez et al 1993;Zhang et al 2008). However, differences in litter N content and C:N ratios as a result of fertilization (Sanchez 2001) or repeated prescribed fire application (Ficken and Wright 2017) have been reported to have minimal impacts on decomposition rates within pine stands in the southern United States. Although Sanchez (2001) found little impact of litter quality on decomposition, he did find that litter quality and chemistry affected nutrient dynamics within decomposing loblolly pine (Pinus taeda L.) litterfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation